1960
DOI: 10.1126/science.131.3410.1374
|View full text |Cite
|
Sign up to set email alerts
|

On the Thermal Boundary Layer of the Ocean

Abstract: Measurement of the long-wave infrared radiation from the top 0.1 mm of the evaporating ocean demonstrates the existence of a cool surface layer characterized by departures of as much as 0.6 degrees C from the "surface temperature" found by conventional methods. Being very thin, the layer cools sufficiently rapidly to reestablish itself in less than 12 seconds after disruption by a breaking wave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(35 citation statements)
references
References 2 publications
2
32
0
Order By: Relevance
“…Other laboratory experiments (e.g., Ewing and McAlister 1960) showed that the skin layer can reestablish itself within 9-12 s after it is destroyed by a breaking wave. More recent infrared camera measurements have demonstrated that the skin layer has the ability to restore itself in as little as 1 s (Jessup et al 1997).…”
Section: B Likelihood Of the Existence Of Strong Salinity Stratificamentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratory experiments (e.g., Ewing and McAlister 1960) showed that the skin layer can reestablish itself within 9-12 s after it is destroyed by a breaking wave. More recent infrared camera measurements have demonstrated that the skin layer has the ability to restore itself in as little as 1 s (Jessup et al 1997).…”
Section: B Likelihood Of the Existence Of Strong Salinity Stratificamentioning
confidence: 99%
“…The significance of correcting the cool skin for improving the absolute accuracy of satellite measurements of SST has further stimulated research into the physical processes that determine the near-surface thermal structure and the cause of the skin-bulk difference (e.g., Ewing and McAlister 1960;Hasse 1963;Saunders 1967;Liu and Businger 1975;Liu et al 1979;Katsaros et al 1977;Katsaros 1980;Paulson and Simpson 1981;Robinson et al 1984;Schlü ssel et al 1990;Fairall et al 1996;Wick et al 1996;Katsaros and Soloviev 2004). The appearance of a cool skin layer is due to (i) the combined cooling effects of net longwave radiation, evaporation, and sensible heat flux from the sea surface to the atmosphere and (ii) the transport of heat by molecular conduction in the skin layer instead of turbulent mixing (Hasse 1971;Katsaros 1980;Schlü ssel et al 1990;Fairall et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies have mostly focused on measuring transfer properties averaged over large spatial regions; very few have directly examined the influence of a straining flow on the skin layer. Ewing and McAlister (1960) demonstrated that a turbulent jet directed toward the interface can modify the skin temperature, and Leighton et al (2003) showed that direct numerical simulations of free convection were well described by a surface straining model. However, there has been no quantitative experimental evaluation of the direct influence of a straining flow on the skin temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Most longwave radiation emitted by a water surface is produced in the first 100 ^m below the water surface (McAlister and McLeish, 1969). Ewing and McAlister (1960) found that the temperatures within this layer may differ significantly from that temperature which would be measured with the smallest conventional temperature measuring device placed as close to the water surface as possible. The true surface temperature is generally found to be lower than the bulk water temperature.…”
Section: Pcpymentioning
confidence: 99%